2008
DOI: 10.1177/1524839907307994
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Universal Screening for Domestic Violence in an Urgent Care Community Health Center

Abstract: Given the morbidity and mortality associated with domestic violence (DV), there is international recognition that the health sector has a responsibility to prevent violence. In North America, the health sector has commonly responded by developing protocols for identifying victims of abuse. This utilization-focused evaluation describes the process involved in the implementation of a universal DV screening protocol undertaken by nurses in the urgent care clinic of a community health center. Dealing with the chal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
6
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 23 publications
2
6
0
Order By: Relevance
“…In the practical frame, the challenges to intervention identified include time constraints, lack of resources, and other infrastructure barriers. This confirms some previous findings (Thurston et al, 2009) indicating that barriers to intervention are not easy to overcome. Nevertheless, McColgan et al (2010) noticed in their research that after receiving intimate partner violence training, none of the participants considered "lack of referral sources" or "lack of knowledge" as barriers to violence screening.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…In the practical frame, the challenges to intervention identified include time constraints, lack of resources, and other infrastructure barriers. This confirms some previous findings (Thurston et al, 2009) indicating that barriers to intervention are not easy to overcome. Nevertheless, McColgan et al (2010) noticed in their research that after receiving intimate partner violence training, none of the participants considered "lack of referral sources" or "lack of knowledge" as barriers to violence screening.…”
supporting
confidence: 91%
“…It has been shown that most victims presenting for social and health care are not screened and do not receive intervention (Furniss, McCaffrey, Parnell, & Rovi, 2007;Owen-Smith et al, 2008). Several studies have sought explanations for the low screening rates (D'Avolio, 2011;Thurston et al, 2009;Todahl & Walters, 2011). It has been suggested that social and health care providers fail to ask about domestic violence because of infrastructure barriers: time limitations, insufficient resources, and inadequate institutional support for screening.…”
mentioning
confidence: 99%
“…Although being introduced in some settings, 45,47,50 screening for IPV within health care settings including HIV care centers remains underutilized despite a high prevalence of IPV and its recognition by agencies such as WHO as an important social determinant of health. One of our study participants noted that ''abuse thrives in secrecy and only if a professional initiates a conversation about abuse will a victim disclose.''…”
Section: Discussionmentioning
confidence: 99%
“…Routine screening for IPV has been introduced in family medicine, 45,46 emergency department, 47,48 prenatal care environments, [49][50][51] and HIV care centers 26,52 with mixed results. Reported barriers to disclosure of IPV voiced by patients have included the fear of increasing violence from partners and a lack of sensitivity of the health care workers to deal adequately with IPV issues in a clinical setting when IPV issues are presented.…”
Section: Introductionmentioning
confidence: 99%
“…Similar issues were identified by nurses, including lack of time, lack of training in both assessment and how to respond as well as unique challenges related to their role including pressure from physicians to see patients quickly, presence of family members, language and cultural differences and challenges of screening older clients and clients with mental health issues [16-18]. Other studies of health care practitioners have found that older, more experienced clinicians, and those with histories of exposure to abuse, were more likely to ask about IPV [19].…”
Section: Introductionmentioning
confidence: 99%